Comparative Proteomic Analysis of the Graft Unions in Hickory (Carya cathayensis) Provides Insights into Response Mechanisms to Grafting Process - Xu, Dongbin; Yuan, Huwei; Tong, Yafei; Zhao, Liang; Qiu, Lingling; Guo, Wenbin; Shen, Chenjia; Liu, Hongjia; Yan, Daoliang; Zheng, Bingsong (Frontiers in Plant Science, 2017)
Hickory (Carya cathayensis), a tree with high nutritional and economic value, is widely cultivated in China. Grafting greatly reduces the juvenile phase length and makes the large scale cultivation of hickory possible. To reveal the response mechanisms of this species to grafting, we employed a proteomics-based approach to identify differentially expressed proteins in the graft unions during the grafting process. Our study identified 3723 proteins, of which 2518 were quantified. A total of 710 differentially expressed proteins (DEPs) were quantified and these were involved in various molecular functional and biological processes. Among these DEPs, 341 were up-regulated and 369 were down-regulated at 7 days after grafting compared with the control. Four auxin-related proteins were down-regulated, which was in agreement with the transcription levels of their encoding genes. The Kyoto Encyclopedia of Genes and Genomes analysis showed that the ‘Flavonoid biosynthesis’ pathway and ‘starch and sucrose metabolism’ were both significantly up-regulated. Interestingly, five flavonoid biosynthesis-related proteins, a flavanone 3-hyfroxylase, a cinnamate 4-hydroxylase, a dihydroflavonol-4-reductase, a chalcone synthase, and a chalcone isomerase, were significantly up-regulated. Further experiments verified a significant increase in the total flavonoid contents in scions, which suggests that graft union formation may activate flavonoid biosynthesis to increase the content of a series of downstream secondary metabolites. This comprehensive analysis provides fundamental information on the candidate proteins and secondary metabolism pathways involved in the grafting process for hickory.